Mechanisms of abdominal distension in severe intestinal dysmotility: abdomino‐thoracic response to gut retention. Issue 6 (22nd April 2013) - Barba, E.; Quiroga, S.; Accarino, A.; Lahoya, E. M.; Malagelada, C.; Burri, E.; Navazo, I.; Malagelada, J. ‐R.; Azpiroz, F.
Abstract Background We previously showed that abdominal distension in patients with functional gut disorders is due to a paradoxical diaphragmatic contraction without major increment in intraabdominal volume. Our aim was to characterize the pattern of gas retention and the abdomino‐thoracic mechanics associated with abdominal distension in patients with intestinal dysmotility. Methods In 15 patients with manometrically proven intestinal dysmotility, two abdominal CT scans were performed: one during basal conditions and other during an episode of severe abdominal distension. In 15 gender‐ and age‐matched healthy controls, a basal scan was performed. Key Results In basal conditions, patients exhibited more abdominal gas than healthy subjects, particularly in the small bowel, and the volume significantly increased during an episode of distension. During episodes of abdominal distension, the increase in abdominal content was associated with increased girth and antero‐posterior abdominal diameter, as well as a cephalic displacement of the diaphragm, which reduced the height of the lung. The consequent reduction in the air volume of the lung was attenuated by an increase in the antero‐posterior diameter of the chest. Conclusions & Inferences Abdominal distension in patients with severe intestinal dysfunction is related to marked pooling of gut contents, particularly in the small bowel. This increase in content is accommodated within the abdominal cavity by a global and coordinated abdomino‐phreno‐thoracic response, involving an accommodative ascent of the diaphragm and a compensatory expansion of the chest wall.